Comparative Analysis of Skeletal Muscle DNA Methylation and Transcriptome of the Chicken Embryo at Different Developmental Stages - Ran, Jinshan; Li, Jingjing; Yin, Lingqian; Zhang, Donghao; Yu, Chunlin; Du, Huarui; Jiang, Xiaosong; Yang, Chaowu; Liu, Yiping (Frontiers in Physiology, 2021)
DNA methylation is a key epigenetic mechanism involved in embryonic muscle development and plays important role in early muscle development. In this study, we sought to investigate the effects of genome-wide DNA methylation by combining expression profiles of the chicken embryonic muscle. Genome-wide DNA methylation maps and transcriptomes of muscle tissues collected from different embryonic development points (E7, E11, E17 and D1) were used for whole-genome bisulfite sequencing (WGBS) and RNA sequencing, respectively. We found that the differentially methylated genes (DMGs) were significantly associated with muscle organ development, regulation of skeletal muscle satellite cell proliferation and actin filament depolymerization. Furthermore, genes TBX1, MEF2D, SPEG, CFL2 and TWF2 were strongly correlated with methylation-caused expression switch. Therefore, we chose the CFL2 gene to explore its function in skeletal muscle satellite cells, and the in vitro experiments showed that CFL2 acts as a negative regulator of chicken skeletal muscle satellite cell proliferation and can induce cell apoptosis. These results provide valuable data for future genome and epigenome studies of chicken skeletal muscle and may help reveal the molecular mechanisms of potential economic traits.